The Minimum Wage and Its Implications to The Open Unemployment Rate Covid-19 Pandemic in West Java - Indriana Damaianti; Ruli Mochammad Chaerudin (Journal of International Conference Proceedings (JICP), 2021)
The escalation of Covid-19 cases in Indonesia really affected employment sector, as seen from the escalation of unemployment rate, especially in West Java. Based on data from Statistics Indonesia (BPS) of West Java Province in February 2021, the escalation in the open unemployment rate reached 8,75 million people. The impact of Covid-19 has also made business performer experience a decreasing income, making it difficult to pay wages. Unemployment causes psychological effects on individuals and reduces the level of welfare. The purpose of this study was to determine the effect of the minimum wage on the open unemployment rate in West Java. This study is associative research using a quantitative approach. The analytical method used in this study is simple regression analysis using secondary data obtained from Statistics Indonesia (BPS) in 2015-2020 in West Java Province. The results showed that the minimum wage has no effect on the open unemployment rate. It is expected that the wage policy be able to provide a balance between the capability of the company and a decent life